Research Progress and Development Direction for Health Evaluation of Rivers and Lakes - ZHOU Xingchi; WEI Junbiao; WANG Gaoxu; WU Yongxiang; XU Yi (Renmin Zhujiang, 2024)
The health evaluation of rivers and lakes is a crucial means for diagnosing the health status of water bodies and shorelines and guiding the ecological restoration of rivers and lakes. Therefore, this study reviewed the current state of research and proposed future development directions for the health evaluation of rivers and lakes, providing scientific reference and support for river and lake management in China. The study focused on four aspects: the health connotation of rivers and lakes, health evaluation scales, evaluation content and indicators, and evaluation methods and models. The development and change of health evaluation of rivers and lakes in China and abroad were summarized. The results indicate that: ① The health connotation standards for rivers and lakes with different functions should meet the current social choices rather than blindly pursuing high standards. ② Existing river and lake health evaluation scales are concentrated at the medium scale, lacking research on methods for converting between different scales. ③ The evaluation indicators for river and lake functions insufficiently cover the various types of river and lake functions and need further expansion. ④ The establishment of indicator evaluation standards is insufficient, requiring continuous improvement of relevant standards and norms. ⑤ Indicator weights are fixed, while the evaluation focus varies for different types of rivers and lakes. To address the deficiencies in current research and the practical issues in China's evaluation work, this study proposes a standardized river and lake health evaluation system based on river and lake functions.